2012
DOI: 10.3390/ijms13056026
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Glucans Improve Growth, Viability and Colonization of Probiotic Microorganisms

Abstract: Probiotics, prebiotics and synbiotics are frequently-used components for the elaboration of functional food. Currently, most of the commercialized probiotics are limited to a few strains of the genera Bifidobacteria, Lactobacillus and Streptococcus, most of which produce exopolysaccharides (EPS). This suggests that the beneficial properties of these microorganisms may be related to the biological activities of these biopolymers. In this work we report that a 2-substituted-(1,3)-β-d-glucan of non-dairy bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 41 publications
4
97
1
1
Order By: Relevance
“…Concerning beta-glucan our results differ from previous findings. Ruso and colleagues (2012) demonstrated that beta-glucans increased the growth, viability and colonization ability of probiotic microorganisms (Russo et al, 2012). We suggest that the reason for these different effects is the origin of the substance used for the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning beta-glucan our results differ from previous findings. Ruso and colleagues (2012) demonstrated that beta-glucans increased the growth, viability and colonization ability of probiotic microorganisms (Russo et al, 2012). We suggest that the reason for these different effects is the origin of the substance used for the studies.…”
Section: Resultsmentioning
confidence: 99%
“…EPS can affect the composition of the microbiota without being degraded (21), and it remains to be shown whether the EPS from P. parvulus 2.6 is partially or completely degraded by the microbiota or not. Russo et al previously showed that the EPS from P. parvulus 2.6 could be used as the sole carbon source by some probiotic strains, indicating at least partial degradation (22).…”
Section: Discussionmentioning
confidence: 99%
“…cremoris NIZO B40 could be fully recovered in rat feces (20), and the EPS from Lactobacillus rhamnosus RW-9595 M was not degraded but still decreased the lactobacillus count (21). The EPS [a 2-substituted-(1, 3)-␤-D-glucan] produced by Pediococcus parvulus 2.6, can be used as a substrate by different probiotic Lactobacillus strains (22).…”
mentioning
confidence: 99%
“…β-Glucans from microbial origin have been investigated for their prebiotic features and were proved to advantage Bifidobacterium spp., to decrease cholesterol levels in humans (Mårtensson et al, 2005) and to improve rheology and texture of fermented foods (Mårtensson et al, 2002). Moreover, a 2-substituted-(1,3)-β-D-glucan of bacterial origin was shown to ameliorate in vitro the adhesion of Lactobacillus strains to the human intestinal epithelium, thus suggesting that it could contribute to improve colonization and persistence of probiotics into the host, with related beneficial effects (Russo et al, 2012). Food matrices containing barley β-glucans were reported to improve growth and probiotic features of different Lactobacillus strains during both unstressed conditions and after exposure to in vitro simulation of the digestive tract.…”
Section: β-Glucans and Probioticsmentioning
confidence: 99%